A decision support tool to assist with lifetime extension of wind turbines. (May 2018) - Rubert, T.; McMillan, D.; Niewczas, P.
Abstract: This paper is aimed at analysing the levelised cost of energy (LCOE) of onshore wind turbine generators (WTGs) that are in operation beyond their design lifetime. In order to do so, the LCOE approach is introduced and input parameters are discussed for a UK deployment. In addition, a methodology is presented to support economic lifetime extension and investment decision making at the end of an asset's design lifetime. As part of a case study, a wind farm consisting of six 900 kW WTGs is subjected to different combinations of i) lifetime extension (5–15 years), ii) input assumptions (pessimistic, central, optimistic), and iii) reinvestment types (retrofits). Results indicate that in the central lifetime extension scenario, LCOE estimates of 22.40 £/MWh are achievable. Graphical abstract: Image 1 Highlights: A break down structure of lifetime extension assessment and its costs are presented. LCOE model input parameters are reviewed & discussed for the UK. A wind farm with a capacity of 5.4 MW, consisting of six 900 kW rated turbines is subjected to lifetime extension scenarios. LCOE of 22.40 £/MWh are achievable for the life extended period. LCOE results are compared to the revenue stream in a non-subsidised market and under the Renewable Obligation respectively.